CONSERVATION OF BIO-CONTROL AGENTS IN COTTON, GOSSYPIUM HIRSUTUM L. FIELD BY FOOD SUPPLEMENTS FOR INSECT PESTS MANAGEMENT - Ahmad, N.; Sarwar, M.; Muhammad, R.; Tofique, M.; Wagan, M. S. (The Nucleus, 2011)
The study reports the use of artificial food sprays to conserve the parasitoids and predators for the management of insect pests in cotton field. Cotton crop was treated with bio-control agents, Chrysoperla carnea and Trichogramma chilonis alongwith different food attractants such as protein hydrolysate and sugar alone and in combination in a randomized complete block design. Each treatment was applied on one-acre field with three replications. Results showed that the chemicals tested helped in increasing the populations of beneficial insects including; C. carnea, T. chilonis and Orius spp., in the field. The populations of C. carnea and T. chilonis were found the highest in the combined treatment of protein hydrolysate and sugar as compared to other treatments where protein hydrolysate and sugar were used separately. However, the population of Orius spp. was higher in the treatment where only sugar solution was sprayed as food supplement. Consequently, incorporation of food supplements in the trial increased the establishment of natural enemies and subsequently the predation/ parasitism percentage enhanced on the insect pests of cotton.